Designing a mobile app to support a healthy lifestyle (MAS-HeaL) for type-2 diabetes patients in Malaysia - Imhemed, Serag M.; Kamaruddin, Azrina; Hasan, Sa’adah (Medwell Journals, 2017)
M-Health applications targeting diabetics have not only been inapplicable and inappropriate to people’s cultures, context and experiences. Many mobile application designs show general design that fits all types of diabetes and all types of users regardless of their cultures and countries. Therefore, the aim of this research study is to establish the requirements for type-2 diabetes in Malaysia using the user-centered approach. The result of the evaluation shows that the proposed application has been proven in sum to be effective in achieving its objectives, efficiency and satlsfactory with regards to the user requirements. In addition, the proposed application will assist developers and other researchers to design and implement an effective, highly usable and ease to use M-Health application for consumer health technology for Asian type-2 diabetes patients.